2013
DOI: 10.17305/bjbms.2013.2360
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by grape seed extract (Vitis vinifera) in oral squamous cell carcinoma

Abstract: Development of novel therapeutic modalities is crucial for the treatment of oral squamous cell carcinoma (OSCC). Recent scientifi c studies have been focused on herbal medicines as potent anti-cancer drug candidates. Th is study is the fi rst to investigate the cytotoxic eff ects and the mechanism of cell death induced by grape seed extract (GSE) in oral squamous cell carcinoma (KB cells). MTT (-(,-dimetylthiazol--yl)-, diphenyltetrazolium bromide) and trypan blue assays were performed in KB cells as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Apoptosis is characterized by morphological changes for instance, cell shrinkage, membrane blebbing, chromatine condensation, DNA fragmentation and loosing organelles position in cytoplasm (Aghbali et al 2013;Galluzzi et al 2007). It has been shown that some plants such as saffron, curcumin and Ginger suppressed carcinogenic progress through induction of apoptosis (Bakhshi et al 2008Bathaie et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is characterized by morphological changes for instance, cell shrinkage, membrane blebbing, chromatine condensation, DNA fragmentation and loosing organelles position in cytoplasm (Aghbali et al 2013;Galluzzi et al 2007). It has been shown that some plants such as saffron, curcumin and Ginger suppressed carcinogenic progress through induction of apoptosis (Bakhshi et al 2008Bathaie et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, MCF-7 cells were treated with alcoholic extract of Berberis (1.5 and 3 mg/ml) for 48 h. DNA samples were isolated after cell lysis according to previous studies (Aghbali et al 2013;Samarghandian and Shabestari 2013). The samples were analyzed by electrophoresis on 1.5 % agarose gel in TAE buffer containing 0.5 lg/ml ethidium bromide.…”
Section: Dna Fragmentation Assaymentioning
confidence: 99%
“…), apoptotic effects in tumour cells (Aghbali et al . , Yen et al . ) and effects on bone metabolism (Ishikawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Proanthocyanidins (PACs) have been investigated in the areas of medical and nutritional health for various biological effects, such as antioxidant capacity (Houde et al 2006, Katsuda et al 2015, apoptotic effects in tumour cells (Aghbali et al 2013, Yen et al 2015 and effects on bone metabolism (Ishikawa et al 2005, Yahara et al 2005. In dentistry, the antibacterial capacity of PACs has been assessed in endodontics (Ghonmode et al 2013) and periodontics (Houde et al 2006, Mageshwaran et al 2012) and more recently as a crosslinker , 2010 in Restorative Dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is among the most prevalent oral cancers, the risk of which is increasing in individuals under 40 years old, particularly in developed countries (Aghbali et al, 2013). The proposed risk factors include micronutrient deficiencies, chronic trauma, poor oral hygiene, and some specific microorganisms like viruses (Lauritano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%